Esthetic and Functional Rehabilitation with Immediate Implant Placement Using 3D Printing, Grafts, and Biomaterials: Clinical Case Report. - Batista, João Pedro Oliveira de; Matos, Jefferson David Melo de; Morais, Tales Cyríaco; Oliveira, Samantha de Almeida Ferreira; Ramos, Umberto Demoner; Lopes, Guilherme da Rocha Scalzer; Andrade, Valdir Cabral (Brazilian Journal of Implantology and Health Sciences, 2025)
This report describes a clinical case involving a minimally traumatic tooth extraction followed by immediate implant placement in the region of an upper premolar, associated with alveolar grafting using a synthetic biomaterial and an autogenous graft harvested from the maxillary tuberosity. A 38-year-old male patient presented with a vertical root fracture in tooth 25. Atraumatic extraction was performed, followed by alveolar curettage and immediate placement of a conical implant (Ø 3.5 × 13 mm). The buccal gap was filled with hydroxyapatite combined with β-tricalcium phosphate and autogenous bone graft obtained from the maxillary tuberosity. An immediate provisional acrylic resin crown was installed with occlusion deactivated. After six months, a definitive zirconia crown with a lithium disilicate infrastructure was fabricated and cemented. Immediate post-extraction implant placement has emerged as an effective treatment strategy, particularly in esthetic zones, allowing for preservation of bone and gingival architecture, reduction of physiological resorption, and enhanced esthetic predictability. The immediate approach, when combined with biomaterials and autogenous grafts, proved to be effective for both functional and esthetic rehabilitation in this case, ensuring preservation of peri-implant tissues and yielding an excellent clinical outcome.